The comprehensibility level of the sales and purchase agreement among middle income earners of Malaysia: the legal language perspective / Angeline Ranjethamoney Vijayarajoo, Salmiah Salleh and Chuang Kwei Yin (Institute of Research, Development and Commercialization (IRDC), 2006)
The legal arena has been noted for its specific jargon and exclusive language structures. The public have often felt that the language of the legal entity has been far too pompous and wordy. It has also been said that this whole area of language has actually worked towards creating an exclusive profession – the legal profession, which undoubtedly excludes 'others' from this area. This paper attempts to look at some selected vocabulary and language structures used in one of the many legal documents - the Sale and Purchase Agreement. The paper also looked at some perceptions of people within and outside the legal entity on aspects of language. Those outside the legal entity were confined to middle income earners and represented by the lecturers in UiTM Melaka. As for the respondents who belonged to the legal entity, these comprised lawyers selected at random from the states of Negeri Sembilan and Melaka. The findings of this research revealed that members outside the legal entity felt that the language structures and legal jargon were difficult to understand and given a choice, would opt for simpler, and more straightforward type of writing and language. On the other hand, those within the legal entity, that is, mainly the lawyers, they felt that the structures and jargon used in this document were appropriate and were generally quite satisfied with the present state of affairs. It is interesting to note and perhaps significant to this research that there were some respondents who felt that they were unhappy with the present state of the language, just as the respondents from the non legal category.